Application of Exergy Analysis in Flue Gas Condensation Waste Heat Recovery System Evaluation - Le Zhang; Huixing Zhai; Jiayuan He; Fan Yang; Suilin Wang (Energies, 2022)
Flue gas condensation heat recovery technology has a good technical and economic performance in industrial exhaust gas waste heat recovery. Thermal efficiency analysis is the traditional analysis method for the flue gas condensation heat recovery system but it cannot reflect the recovered heat degree. Exergy analysis, which can reflect the recovered energy heat degree, was first applied to the evaluation of a flue gas condensation waste heat recovery system in this paper. The calculation method of wet flue gas exergy is more complex as both a heat and mass transfer is presented. Flue gas waste heat exergy efficiency (EE) and the flue gas waste heat exergy utilization rate (EUR) were proposed as the evaluation indexes for exergy analysis. The exergy analysis method was applied to the comparative evaluation of three recovery schemes in a practical project. The results show that when the water vapor content of wet flue gas is less than 10%, the condensed water exergy can be neglected when calculating EE. The EUR could be used as a comprehensive index for comparing different waste heat recovery schemes, and EE could be used to judge whether the energy grade of heat exchange equipment was seriously decreased. Exergy analysis could effectively make up for the deficiency of thermal efficiency analysis that could not reflect the waste heat grade utilization. Exergy analysis and thermal efficiency analysis are recommended to be used simultaneously to make a more comprehensive analysis and evaluation of the system.